Taking up the gauntlet: fictionists in the Turkish parliament - Çimen Günay (European Journal of Turkish Studies)
Turkey has a long tradition of involvement of men of letters in political transformation processes. Several important figures of literature appear as key names in the history of Turkey who contributed to daily politics, manipulated and challenged it, sometimes with the fiercest discourses. Focusing on some prominent fiction writers who accessed the parliament of Turkey, this article discusses the superposition of the role of a writer and a politician. It sheds a critical eye at their subscription to parliamentary politics, and literary activities during their term of office, and comments on the continuity of certain limiting aspects of the political culture of Turkey that troubled them during their political career.